Conditional cash transfers, payment dates and labor supply: Evidence from Perú - Fernández, Fernando (2013)
We assess the effects of a Conditional Cash Transfer program on adult labor supply in Peru. The program, named Juntos, lacks an experimental design so we rely on a sort of “natural experiment”. Instead of comparing treated and non-treated households, our strategy exploits within-municipality variation in the distance between payment dates of Juntos and interview dates of the Peruvian National Household Survey. We find that having received the cash transfer two weeks before the interview causes a reduction of 6 hours of work of recipients during the week prior to the survey. These effects are larger for married women and for mothers with children aged 5 or less. In addition, results are robust to different specifications and changes in the sample.